In vitro induction of TNF-alpha by Ochratoxin A - Al-Anati, Lauy Mohammad Mahmood; Justus Liebig University Giessen (My University, 2006)
Tumor necrosis factor alpha TNF-alpha is a pro-apoptotic cytokinewhich is produced by a wide variety of cell types in response to variousinflammatory stimuli. It promotes the pathogenesis of several health disorders,in particular those related with chronic liver diseases. TNF-alpha is producedmainly by macrophages. That is why liver is considered a major source ofwhole body TNF-alpha, particularly if exposed to gut derived bacterial endotoxins (LPS). Also the liver is continuously exposed to the highest concentration of OTA via portal vein, and considered one of the important OTA-target organs.

Tumornekrosefaktor alpha (TNF-alpha) ist ein pro-apoptotischesCytokin, das von einer großen Anzahl von Zelltypen als Antwort aufEntzündungsreize gebildet wird. Es fördert die Pathogenese mehrererKrankheiten, vor allem solcher, die mit chronischen Lebererkrankungeneinhergehen. TNF-alpha wird überwiegend von Makrophagen gebildet. Die Leberist dann eine Hauptquelle, wenn aus dem Darm resorbierte bakterielleEndotoxine (LPS) auf sie einwirken. Allerdings ist die Leber auch einerständigen Belastung mit hohen Konzentrationen von Ochratoxin A (OTA) überdie Pfortader ausgesetzt und stellt daher ein wichtiges Zielorgan diesesMycotoxins dar.
Keywords: ddc:630